(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The fibre characteristics of five Spondia mombin stands were studied to determine their suitability for pulp and paper production. Wood slivers obtained parallel to grain at three (3) different positions along the bole were macerated in combined identical amounts of glacial acetic acid plus hydrogen peroxide under heat at between 80-100o C. Macerated fibres were washed clean of mixture and mounted on slide for microscopic examination of fibre characteristics. Completely Randomized Design (CRD) was employed for the experiment. Data were analysed using one-way Analysis of Variance (ANOVA) while, the Duncan’s Multiple Range Test (DMRT) was used to separate means of significant differences among the treatments. Results show that significant differences existed in fibre characteristic of sampled trees, however the fibre length ranged from 0.98-1.0 mm, fibre diameter (18.22-21.47 um), lumen width (10.90-12.98 um) and cell wall thickness (3.86-4.60 um). Significant differences were also observed among the derived fibre characteristics, the Runkel ratio ranged from 0.66-8.89, elasticity coefficient (57.22-60.50 %), coefficient of rigidity (19.78-22.24 %), slenderness ratio (43.27-46.5). This implied that, the fibres of S. mombin were short and elastic which make the wood species an appropriate raw material for pulp and paper making especially when blended with other long fibre species.